The Differences of the Behavioral Factors of Midwifes in UCI village and non UCI - Siti Fatma Wati; Chatarina Umbul Wahjuni (Jurnal Berkala Epidemiologi, 2014)
Around 2-3 million in all age groups die each year from vaccine-preventable disease, namely diphtheria, pertussis, tetanus and measles. It happened because of the target of Universal Child Immunization (UCI) in the village has not increased. One of the causes of not achieving the UCI target is from the officer factor. This study aims to determine differences in the characteristics and behavior of officers in UCI and non-UCI villages in Pasuruan District. This research was carried out using a cross-sectional study design. The sample in this study was 76 village midwives. Sampling using a stratified random sampling method. The data obtained were analyzed using the chi-square statistical test. The dependent variable is the UCI Village Status. The independent variable is the characteristics of the village midwife (age, educational background, length of service, employment status, training, and dual tasks), level of knowledge, attitudes, and actions. The results of this study indicate that there are significant differences in the length of work (p = 0.023), employment status (p = 0.030), multiple tasks (p = 0.013), level of knowledge (p = 0.003), actions (p = 0.017) and village midwife behavior (p = 0.045) in UCI and non-UCI villages. The conclusion of this study is that there are differences including factors of length of service, employment, dual tasks, level of knowledge, actions and behavior of village midwives in the UCI and non-UCI Villages, so there is a need for policies so that the Village Midwife focuses on running the program in accordance with her area of expertise.